Konstruksi Hukum Ekonomi Syariah Dalam Fiqh Anggaran Yang Bebasis Akuntansi Syariah - Agus Arwani (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2016)
The current global economic developments have implications for the welfare state. Limits and strength of the nation-state is fading, dispersed to the locality, independent organizations, civil society bodies supra-national (such as NAFTA or the European Union), and multinational corporations. Iin his book Mishra Globalization and Welfare State that globalization has limited the capacity of the nation-state in conducting social protection. One mode of latent corruption done is to inflate the budget or mark-up budget of raising the budget value than the actual value. Problems in this paper how the economic law of Islam respond to the phenomenon of corruption budget? How urgency and fiqh function of the budget in anticipation of corruption in Indonesia?. Through the budget, organization communicates management plans to all members of the organization, coordinating the activities of various parts of the organization, assigning responsibility to the manager, also obtained a commitment from the manager which is the basis for evaluating the performance of managers. Efforts should be made to anticipate and eradicate corruption in Indonesia, not merely intensified the inspection, investigation and arrest criminals only. Efforts to combat corruption and anticipation is not just by intensifying the campaign to strengthen a person's moral values. But building a budget fiqh ala Indonesia as a system for monitoring and controlling the budget both formal and community mechanisms, it should be held, despite the efforts of relatively still questionable results. It can happen because it will be many challenges and obstacles of the parties who are familiar with corruption. Solutions to uphold the integrity of the zone free / corruption of an institution by using sharia accounting principles in the management of the budget. Concrete forms of accounting shari'ah should be able to present a financial statement or budget management that is based on fairness, honesty, and truth as a form of implementation of the responsibility to fellow human beings and execution of commands (liabilities) of God.